Compressive Stockings After Hindfoot and Ankle Surgery. Issue 3 (14th September 2018) - Grubhofer, Florian; Wirth, Stephan
Category: Hindfoot Introduction/Purpose: Swelling and pain are common after foot and ankle procedures. We hypothesized that compressive stockings (CS) treatment after hindfoot surgery would positively influence patient outcomes. Methods: We undertook this randomized controlled trial in 87 consecutive patients to analyze the clinical effect of CS after hindfoot and ankle surgery and evaluate CS-wearing compliance using sensors that were implanted into CS. Ankle swelling, pain status, quality of life (SF-36 score), and the American Orthopaedic Foot & Ankle Score (AOFAS) were set as the primary end points. The CS wearing time in hours and percentage were investigated as the secondary end points. All participants with CS (group I) were informed about the implanted sensor after the CS were taken off. A subgroup analysis of group I was performed to detect differences between patients with high vs low compliance. Results: At 12 weeks, the results of ankle swelling (mean 234 mm in group I and 232 mm in group II), pain in the visual analog scale (1.7 group I vs 1.9 in group II), the SF-36 score (38 points in group I vs 30 points in group II), and the AOFAS score (a mean of 76 points in both groups) showed no statistical differences between the 2 groups. The mean wearing time was 136 (range, 0-470) hours, which corresponds to a compliance rate of 65%. Sixteen participants had high compliance (>80%, >170 hours), and 21 patients had low or noncompliance. The clinical results of patients with high wearing compliance were not significantly better compared to the results of patients with low compliance. Conclusion: CS therapy after ankle and hindfoot surgery was associated with a low wearing compliance and did not influence ankle swelling, function, pain, and the quality of life compared to the control group. Furthermore, the clinical results of patients with high compliance were not better compared to the results of patients with low or noncompliance wearing behavior.